GelMA Core–Shell Microgel Preparation Based on a Droplet Microfluidic Device for Three-Dimensional Tumor Ball Culture and Its Drug Testing - Xindong Yang; Yi Xu; Dongchen Zhu; Xianqiang Mi (Molecules)
Gelatin methacrylate (GelMA) microgels serve as promising bioscaffolds for tissue engineering and drug screening. However, conventional solid GelMA microgels often exhibit limited mass transfer efficiency and provide insufficient protection for embedded cells. In this study, we developed a droplet-based microfluidic platform to fabricate core–shell structured GelMA microgels. This system enabled precise control over microgel size and core-to-shell ratio by modulating flow rates. Encapsulation of A549 cells within these core–shell microgels preserved cellular viability and facilitated the formation of three-dimensional tumor spheroids. These outcomes confirmed both the protective function of the core–shell architecture during encapsulation and the overall biocompatibility of the microgels. The developed GelMA core–shell microgel system presents considerable applicability in research domains such as organoid modeling and high-throughput pharmacological screening.